Granadaene Photobleaching Reduces the Virulence and Increases Antimicrobial Susceptibility of Streptococcus agalactiae. (8th February 2021) - Jusuf, Sebastian; Dong, Pu‐Ting; Hui, Jie; Ulloa, Erlinda R.; Liu, George Y.; Cheng, Ji‐Xin
Abstract: Streptococcus agalactiae, also known as Group B Streptococcus (GBS), is increasingly recognized as a major cause of soft tissue and invasive diseases in the elderly and diabetic populations. Antibiotics like penicillin are used with great frequency to treat these infections, although antimicrobial resistance is increasing among GBS strains and underlines a need for alternative methods not reliant on traditional antibiotics. GBS granadaene pigment is related to the hemolysin/cytolysin of GBS, which is critical for the pathogenesis of GBS diseases. Here, we show that photobleaching granadaene dampens the hemolytic activity of GBS. Furthermore, photobleaching of this antioxidant was found to increase GBS susceptibility to killing by reactive oxygen species like hydrogen peroxide. Treatment with light was also shown to affect GBS membrane permeability and contribute to increased susceptibility to the cell membrane‐targeting antibiotic daptomycin. Overall, our study demonstrates dual effects of photobleaching on the virulence and antimicrobial susceptibility of GBS and suggests a novel approach for the treatment of GBS infection. Abstract : Streptococcus agalactiae, also known as Group B Streptococcus (GBS), is a major cause of soft tissue infections in vulnerable populations. GBS commonly expresses a granadaene pigment that is not only responsible for its orange coloration, but also contributes to the hemolytic activity, antioxidant activity and membrane stability of GBS. Exposure to 430 nm light is capable of bleaching this pigment and reducing the hemolytic activity of GBS, as well as rendering GBS more susceptible to reactive oxygen species and antibiotics such as daptomycin. Pigment photobleaching offers a potentially nonantibiotic reliant method of increasing GBS antimicrobial susceptibility and lowering virulence.